Manajemen Perubahan Dan Inovasi Upaya Meningkatkan Daya Saing Suatu Organisasi - Amwa, Djauky Ridho; Aslami, Nuri (Jurnal Manajemen Akuntansi (JUMSI), 2022)
As humans we live in a world full of change. Changes are interpreted to include, for example, changes in attitudes, value and assessment systems, changes in work procedures and methods, changes in the equipment used, changes in thinking methods, and changes in behavior. In short, humans need to keep getting used to change and the demands of change. Change can be evolutionary, but it can also be revolutionary. It should be reminded that not all changes that occur will lead to a better situation, until in a better case it is better than the previous situation. Thus, we can say that the change still has meaning, the changing of the previous condition becomes the next state. The transition from the initial state to the later state requires a transformation process, which does not always run smoothly, considering that changes are often accompanied by various conflicts that arise. Change management aims to control the effects and minimize the impact of losses that can occur on the industry, change management with a human approach that provides the best impact. This study aims to provide an understanding of innovation and change management that can provide efforts to increase competitiveness in an organization. The author uses a qualitative approach that comes from valid articles, scientific journals, and books.